Review Papers for Journal of Risk and Financial Management (JRFM) (Journal of Risk and Financial Management, 2020)
The Journal of Risk and Financial Management (JRFM) was inaugurated in 2008 and has successfully continued publishing, with Volume 13 in 2020. Since the journal was established, JRFM has published in excess of 580 topical and interesting theoretical and empirical papers in financial economics, financial econometrics, banking, finance, mathematical finance, statistical finance, accounting, decision sciences, information management, tourism economics and finance, international rankings of journals in financial economics, and bibliometric rankings of journals in cognate disciplines. Papers published in the journal range from novel technical and theoretical papers to innovative empirical contributions. The journal wishes to encourage critical review papers on topical subjects in any of the topics mentioned above in financial economics and in cognate disciplines.